Divergent Coupling of Alcohols and Amines Catalyzed by Isoelectronic Hydride MnI and FeII PNP Pincer Complexes. Issue 35 (27th July 2016) - Mastalir, Matthias; Glatz, Mathias; Gorgas, Nikolaus; Stöger, Berthold; Pittenauer, Ernst; Allmaier, Günter; Veiros, Luis F.; Kirchner, Karl
Abstract: Herein, we describe an efficient coupling of alcohols and amines catalyzed by well‐defined isoelectronic hydride Mn I and Fe II complexes, which are stabilized by a PNP ligand based on the 2, 6‐diaminopyridine scaffold. This reaction is an environmentally benign process implementing inexpensive, earth‐abundant non‐precious metal catalysts, and is based on the acceptorless alcohol dehydrogenation concept. A range of alcohols and amines including both aromatic and aliphatic substrates were efficiently converted in good to excellent isolated yields. Although in the case of Mn selectively imines were obtained, with Fe—exclusively monoalkylated amines were formed. These reactions proceed under base‐free conditions and required the addition of molecular sieves. Abstract : Efficient coupling of alcohols and amines catalyzed by well‐defined isoelectronic hydride Mn I and Fe II complexes is described. A range of alcohols and amines, including both aromatic and aliphatic substrates, was efficiently converted giving in the case of Mn selectively imines, whereas with Fe, exclusively amines were formed (see scheme).